A COMPARATIVE STUDY OF REGENERATIVE BRAKING EFFICIENCY BETWEEN AUTOMATED AND HUMAN DRIVEN ELECTRIC VEHICLES TO MINIMIZE BATTERY DEGRADATION - Almataev, Tojiboy; Zokirjonov , Azizbek (Techscience uz - Topical Issues of Technical Sciences, 2025)
Recently, lithium-ion batteries has been becoming essential components in electric vehicles and hybrid electric vehicles however, their degradation significantly impacts the battery's lifespan, reliability, safety, and overall performance. Accurately evaluating and quantifying the extent of degradation is crucial for determining the true state of health of lithium-ion batteries. As a key component of electric vehicles, the regenerative braking system improves energy efficiency and extend the range of electric vehicles by capturing kinetic energy during braking and converting it into stored energy in the batteries or other storage systems. In this comparative study, regenerative braking efficiency between automated and human driven electric vehicles to review and analyze the chance of minimize battery degradation and assess the battery state of health.